Photometry using Kepler "superstamps" of open clusters NGC 6791 & NGC 6819. Issue Volume 9:Issue S301(2013) (18th February 2014) - Kuehn, Charles A.; Drury, Jason; Stello, Dennis; Bedding, Timothy R.
Abstract: The Kepler space telescope has proven to be a gold mine for the study of variable stars. Unfortunately, Kepler only returns a handful of pixels surrounding each star on the target list, which omits a large number of stars in the Kepler field. For the open clusters NGC 6791 and NGC 6819, Kepler also reads out larger superstamps which contain complete images of the central region of each cluster. These cluster images can potentially be used to study additional stars in the open clusters. We present preliminary results from using traditional photometric techniques to identify and analyze additional variable stars from these images.